A priori assessment of long‐term productivity of frac‐packed wells for producing natural gas from marine gas hydrate reservoirs. Issue 6 (6th February 2021) - Guo, Boyun; Fu, Chunkai; Liu, Ning
Abstract: This work investigates the feasibility of using frac‐packing techniques to complete wells in marine gas hydrate fields. It focuses on the long‐term well productivity under pseudo‐steady state flow conditions after the gas hydrate reservoir pressure drops to below the hydrate dissociation pressure within the well drainage area. The analytical model proposed by Shan et al. (J Energy Sci Eng, 2020, 8, 1247) for cross‐flow in the fractured region was modified in this study to include the horizontal radial flow in the non‐fractured region of the well drainage area. Methods were developed to predict the fracture geometry and to design proppant size distribution for formation sand/particle control. Sensitivity analyses with the model identified the fracture radius and permeability being the key factors affecting the productivity of frac‐packed wells. Well productivity was found to increase non‐linearly with fracture radius and permeability. The benefit of increasing fracture size drops due to the choking effect near the wellbore and pressure loss inside the fracture. The benefit of increasing fracture permeability diminishes when the fracture permeability is large due to the bottleneck of low reservoir permeability. Gas hydrate wells in the Shenhu area, northern South China Sea, can be elevated to commercial levels of greater than 10 MMscf per day with a proppant injection volume of 110 cubic feet during frac‐packing. Well productivity can be further increased by injecting higher proppant volume to enlarge fracture. This work presents a simple method for assessment of frac‐packing design to improve well productivity in marine gas hydrate reservoirs. Abstract : This work investigates the feasibility of using frac‐packing techniques to complete wells in marine gas hydrate fields. It focuses on the long‐term well productivity under pseudo‐steady‐state flow conditions after the gas hydrate reservoir pressure drops to below the hydrate dissociation pressure within the well drainage area. Methods were developed to predict the fracture geometry and to design proppant size distribution for formation sand/particle control.